Assessment of drug use practices among dermatology out-patients using WHO core drug use indicators - Mukherjee, Shatavisa; Era, Nikhil; Banerjee, Gautam; Tripathi, Santanu Kumar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Considering the economic burden the skin diseases cause owing to its high prevalence, it is of interest to periodically monitor the drug use pattern so as to increase the therapeutic efficacy, decrease adverse effects and provide feedback to prescribers. The present study thus assessed the drug use practices among dermatology outpatients in a tertiary care teaching unit in Eastern India. Methods: The study assessed drug use practices for all prescriptions of patients attending the concerned OPD using WHO core drug use indicators which consist of mainly three domains, prescribing indicators, patient care indicators and healthcare indicators. Results: Total number of drugs in 471 prescriptions was found to be 1050. Number of drugs per prescription varied from 1 to 6 with average of 2.22. The most commonly prescribed drugs were antibiotics, followed by steroids and steroidal combinations. Prescribing indicators revealed that 2.09% drugs were generic prescribing, with about 18.78% of the drugs being prescribed from the WHO essential drug list. The proportion of encounters with at least one antibiotic prescribed was 34.82%. 13.9% drugs actually dispensed from hospital supply, of which all were adequately labelled. Conclusions: Increasing dermatological prescribing has necessitated assessment of their rational usage. Promoting rational drug use policy is recommended for effective healthcare management.